2021
DOI: 10.1371/journal.ppat.1009949
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of transcriptional profiles of Treponema pallidum during experimental infection of rabbits and in vitro culture: Highly similar, yet different

Abstract: Treponema pallidum ssp. pallidum, the causative agent of syphilis, can now be cultured continuously in vitro utilizing a tissue culture system, and the multiplication rates are similar to those obtained in experimental infection of rabbits. In this study, the RNA transcript profiles of the T. pallidum Nichols during in vitro culture and rabbit infection were compared to examine whether gene expression patterns differed in these two environments. To this end, RNA preparations were converted to cDNA and subjecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
39
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(44 citation statements)
references
References 65 publications
5
39
0
Order By: Relevance
“…There is ample evidence the proteins encoded by tp0470 and arp genes are present during infection: Previous studies have shown that the tp0470 transcript is expressed ( Smajs et al, 2005 ; De Lay et al, 2021 ), and sera from infected rabbits ( McKevitt et al, 2005 ) and patients ( Brinkman et al, 2006 ) are reactive to TP0470 protein. The arp transcript is expressed ( Smajs et al, 2005 ; De Lay et al, 2021 ), and the ARP protein was found to be one of the top 10% most abundant proteins by mass spectrometry ( Osbak et al, 2016 ). T. pallidum -infected rabbit sera are reactive to ARP ( McKevitt et al, 2005 ; Liu et al, 2007 ), while sera from infected human patients are weakly reactive to ARP during primary infection ( Brinkman et al, 2006 ).…”
Section: Resultsmentioning
confidence: 99%
“…There is ample evidence the proteins encoded by tp0470 and arp genes are present during infection: Previous studies have shown that the tp0470 transcript is expressed ( Smajs et al, 2005 ; De Lay et al, 2021 ), and sera from infected rabbits ( McKevitt et al, 2005 ) and patients ( Brinkman et al, 2006 ) are reactive to TP0470 protein. The arp transcript is expressed ( Smajs et al, 2005 ; De Lay et al, 2021 ), and the ARP protein was found to be one of the top 10% most abundant proteins by mass spectrometry ( Osbak et al, 2016 ). T. pallidum -infected rabbit sera are reactive to ARP ( McKevitt et al, 2005 ; Liu et al, 2007 ), while sera from infected human patients are weakly reactive to ARP during primary infection ( Brinkman et al, 2006 ).…”
Section: Resultsmentioning
confidence: 99%
“…As the genomics gap is being closed at unprecedented speed for T. pallidum , the application of other “-omics,” mainly transcriptomics and proteomics, will provide complementary information to help identify vaccine candidates ( 32 , 33 ). Only limited work to date has focused on analyzing the T. pallidum transcriptome and proteome ( 32 38 ).…”
Section: Omics and Other Approaches To The Rescuementioning
confidence: 99%
“…In addition to being poorly expressed, selected OMP-encoding genes have been reported to undergo stochastic modulation of gene expression through phase variation, which might contribute to changing the pathogen surface antigenic profile ( 39 , 40 ). To date, a microarray study describing transcriptome of Nichols strain was conducted and found that the RNA transcript of T. pallidum profiles between in vitro culture and rabbit infection were similar ( 33 ). A better understanding of gene regulation and gene expression could lead to exclusion of specific vaccine candidates whose transcription might be turned off with no detriment to the pathogen.…”
Section: Omics and Other Approaches To The Rescuementioning
confidence: 99%
See 1 more Smart Citation
“…T. pallidum protein Tp0136, a fibronectin-binding protein is known to induce fibroblasts to produce MMP9 [ 15 ]. In addition, Tp0136 mRNA transcript levels have been reported to be considerably higher when compared with the rest of the transcriptome during syphilis infection [ 16 , 17 ], suggesting that Tp0136 might have a significant role in the process of T. pallidum infection. Based on this finding, we stipulated that Tp0136 would promote the expression of MMP or TIMP, which in turn might contribute to the imbalance of MMP/TIMP, which can induce T. pallidum invasion and dissemination from the site of entry.…”
Section: Introductionmentioning
confidence: 99%